2021
DOI: 10.3390/biophysica1020010
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Quillaja saponaria Saponins towards Lung Cells Is Higher for Cholesterol-Rich Cells

Abstract: The purpose of the study was to compare cytotoxicity of two Quillaja saponaria bark saponin (QBS) mixtures against two lung cell lines: normal MRC-5 fibroblast cell line and tumor A-549 epithelial cells of lungs’ alveoli. The study, performed both at a macro-scale and in a dedicated microfluidic device, showed that QBS was more toxic to the cell line more abundant in cholesterol (MRC-5). The QBS mixture with higher saponin fraction was found to be more cytotoxic towards both cell lines. The results may help to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Recently, studies have been conducted on the anticancer and antibacterial effects of saponin [11,[65][66][67]. In one study, saponin extracted from the seeds of Madhuca longifolia was used to clean the dental canal.…”
Section: Biological Studies Resultsmentioning
confidence: 99%
“…Recently, studies have been conducted on the anticancer and antibacterial effects of saponin [11,[65][66][67]. In one study, saponin extracted from the seeds of Madhuca longifolia was used to clean the dental canal.…”
Section: Biological Studies Resultsmentioning
confidence: 99%
“…Our recent results suggest that their selectivity might in fact be dictated mostly by the cells’ cholesterol content. We have shown that the mixture of saponins from a Chilean tree Quillaja saponaria Molina (known as Quillaja bark saponis, QBS) is cytotoxic to the cancerous lung cells (A549), but even higher toxicity was observed towards the normal lung cells (MRC-5), which were more abundant in total cholesterol [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oat grains, apart from highly valuable nutritional compounds, contain substances with anti-nutritional and toxic effects, i.e., saponins (avenacosides), which can irreversibly connect to the cell membrane, thus increasing its permeability [9]. Phytic acid present in oat grain may also have a negative health impact, as it has, among others, the ability to block the bioavailability of some micronutrients, such as iron, copper, zinc, or magnesium [10].…”
Section: Introductionmentioning
confidence: 99%